Kesehatan Remaja Pergaulan Bebas Kalangan Remaja Di SMK Negeri 4 Kota Gorontalo - Latara, Farhan; Haryani, Meri; Toa, Moh AlFikri; Pratama, Muh. Ariel; Prasetnya, Dino; Kusuma, Kartadinata; Manorek, Vikri; Lukuta, Abdul; Dalaem, Hendra; Tongkat, Ridonal; Adjana, Rifki; Irawan, Safri (Universitas Negeri Gorontalo, 2025)
Adolescence is the most radiant period of life, a time for self-discovery, yet it is also when many teenagers become trapped in free associations and risky behaviors. Therefore, teenagers require special attention from themselves, their parents, and the surrounding community. This community service activity involved young participants from SMK Negeri 4 in Gorontalo City. The novelty of this activity was in providing direct counseling about the impacts of free associations and free sex on teenagers at SMK Negeri 4. The aim of this activity was to equip teenagers with knowledge and insights regarding the consequences of free associations among youth. The target group consisted of the community and parents of the teenagers, with 25 individuals from SMK Negeri 4 participating. The activity was conducted in the form of a counseling session (lecture), followed by a question-and-answer session. As a result, students at SMK Negeri 4 gained valuable knowledge about handling free associations among teenagers and finding ways to avoid the negative impacts of such behaviors. In conclusion, the counseling on the consequences of free associations and free sex directly contributed to helping teenagers prevent such behaviors and avoid their negative effects.